Performance evaluation of asphalt concrete mixes having copper industry waste as filler - Choudhary J.; Kumar B.; Gupta A. (My University, 2025)
Increase in demand of copper and copper allied products have led to unavoidable generation of billions of tons of copper tailings throughout the globe. This study investigated the possibility of utilizing copper tailings (CT) of Indian origin in place of conventional stone dust as filler in asphalt concrete mixes. Detailed physical, morphological and mineralogical characterization of both fillers was done through specific gravity, plasticity index, methylene blue value (MBV), particle size distribution, German filler values, Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD), hydrophilic coefficient and pH value tests. Thereafter, asphalt concrete mixes containing both fillers were designed using Marshall mix design procedure and their optimum asphalt contents were determined. At their respective OAC's, both mixes were compared on the basis of their stabilities, volumetric properties as well as their performance against various distresses (rutting, cracking, ravelling and moisture susceptibility) using relevant testing procedures. Copper tailing mixes delivered satisfactory Marshall and volumetric properties at relatively lower OAC than conventional mixes, which was attributed to the relatively lower porosity of copper tailings. Also, copper tailings mixes were found to have superior rutting and cracking resistances due to their lower VMA and fineness of copper tailings respectively. However, copper tailing mixes displayed relatively inferior (yet satisfactory) performance than conventional mixes in terms of moisture sensitivity, ravelling resistance, active and passive adhesion. This was due predominance of silica as well as absence of calcium based water insoluble minerals like dolomite in the composition of copper tailings. © 2020 The Authors. Published by Elsevier B.V.